Novel DOA estimation method for coherent wideband LFM signals - Peng,LIUKai-hua LUO; Jie-xiao YU; Yong-tao MA (Tongxin xuebao)
A novel direction of arrival (DOA) estimation method for coherent wideband linear frequency modulation (LFM) signals was proposed.Based on the dechirping property of LFM signal in fractional Fourier domain,a new array data model was constructed,then the matrix reconstruction and MUSIC algorithm were used to estimate the DOA of coherent LFM signals.If there were multiple groups of coherent LFM signals incident,separated them in different energy-concentrated domains first,then carried the DOA estimation on each of the groups.Owing to fully excavating the time-frequency information included in observed signals,this method has good resolution ability and anti-noise performance,and the number of DOA that can be resolved is also increased.In addition,this method has no array redundancy and aperture loss,and can be applied to arbitrary array manifold.Simulation results show that this method can obtain nearly 8dB signal-to-noise ratio gain compared with the conventional method.